The structure of authorized spaces for the storage of agricultural production in Romania 2014 - Ana-Ruxandra Micu; Ioan Niculae Alecu; Valentina Tudor; Marius Mihai Micu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
This work aims to present a study that consisted of researching, interpreting of statistical data, combined with theoretical aspects that allowed a brief but pragmatic analysis of storage spaces existing in Romania at present and assessing the deficit storage space of the total vegetal production of the main categories of vegetal crops in 2014. Thus, knowing these matters there can be developed national strategies to prevent imbalances and distortions which can appear in the correct formation that prices of crop production, representing a real advantage for agricultural producers in Romania. Thus, at the end of 2014 in Romania for a total of 25,602,657 tons of total agricultural production of the main crops and a total storage capacity of 20,817,496 tons, according to the working hypothesis mentioned, it follows a deficit of 4,785,161 tons of storage.
Keywords: 330; warehouse; storage deficit; agricultural production; Romania